Drinking as a Particular Socio-Spatial Practice in the New Capital of the Turkish Republic - Fatma Eda Çelik (Revue des Mondes Musulmans et de la Méditerranée)
The act of drinking enjoyed a multi-layered history in the Ottoman Empire, taking into consideration that drinking is a social practice formed mainly through “lived experience”. Indeed, it underwent considerable changes during the 19th and early 20th centuries, affecting all Muslims. İstanbul, the capital city of the Empire, became the archetype of this change. However, Ankara deserves some closer scrutiny as it is the most obvious setting for the expression of a profound transformation of drinking practices of an Anatolian city and as it witnessed a transition to the new capital of the Turkish Republic. This examination enables us to question and reconsider the ideal types of imperial past-modern republic, centre-periphery, secular-conservative, bureaucracy-society and the moment of change in the light of socio-spatial practice of drinking places. “Perceived”, “conceived”, and “lived” experiences of space shows that, above these typologies, drinking practices of Ankara changed over time under the influence of political and bureaucratic decisions, economic development, local notables, social upheavals and dynamic class formation.